Hubungan Dukungan Suami dengan Kepatuhan Ibu dalam Penggunaan Kontrasepsi Suntik pada Masa Pandemi COVID-19 - I Gusti Ayu Istri Prema Devi; Ika Widi Astuti; Ida Arimurti Sanjiwani; I Gusti Ayu Pramitaresthi (Jurnal Gema Keperawatan, 2022)
The Covid-19 pandemic has caused various problems, one of them is the population sector. The problem of increasing the number of pregnancies, increasing contraceptive dropout rates, and the risk of Baby Booms in Indonesia has made the government recommend that reproductive age couples comply with the use of contraception during the Covid-19 pandemic. The implementation of the Covid-19 prevention protocol has made it difficult for contraceptive acceptors to get services. One form of contraception that requires repeat visits to health workers is injectable contraceptives. Compliance with the use of injectable contraception is realized through the accuracy of the acceptor in re-injecting according to the schedule. Husband's support is one of the factors that can affect adherence to the use of injectable contraceptives. This study aims to determine the relationship between husband's support and adherence to injecting contraceptive use. This research is a correlative analytic study using a cross sectional approach. Research respondents as many as 50 people obtained through non-probability sampling with purposive sampling technique. The instruments used were husband's support questionnaire and re-injection visit card. Data analysis using Chi-square test. The results showed that there was a significant relationship between husband's support and adherence to injecting contraceptive use (p = 0.000; OR = 29.3; 95% CI 6.2 - 138.781). Acceptors who received support from their husbands had 29,3 times more risk of being obedient in using injectable contraception than acceptors who did not receive support from their husbands. This research expects the need for husband involvement in every reproductive health planning of each family member.